PENGANGGARAN BERBASIS MUTU DALAM MENDUKUNG AKREDITASI LEMBAGA PENDIDIKAN - Sinaga, Salwa Riswanda; Sohiron, Sohiron (STKIP Pesisir Selatan, 2026)
This study aims to describe and analyze the concept and practice of quality-based budgeting as a strategy to support the achievement of educational accreditation and improve institutional performance. The method used is a literature review, analyzing various scientific sources, including books, journal articles, and policy documents relevant to educational budgeting, quality management, and accreditation standards. The study results indicate that quality-based budgeting functions not only as a mechanism for allocating financial resources but also as a strategic instrument linking budget planning to the fulfillment of quality standards and accreditation indicators. This approach has been proven to promote transparency, efficiency, and effectiveness in financial management, while strengthening the internal quality assurance system of educational institutions. The discussion emphasizes that the integration of budgeting and quality management is crucial because accreditation assesses the conformity between educational inputs, processes, and outputs. Therefore, the implementation of quality-based budgeting contributes to increased institutional accountability and the sustainability of educational quality. These findings imply the need for quality-oriented financial management policies as a basis for achieving optimal and sustainable accreditation outcomes.